Kilka uwag o genezie i roli Sądu Sesji w Królestwie Szkocji (1532–1707) - Szymura, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The purpose of this article is to illustrate the origins and evolution of the central court of the Kingdom of Scotland from its inception in 1532 until the end of the Kingdom as an independent entity of international law following its establishment in 1707 of the United Kingdom of Great Britain. The analysis of the structure of the court is based on the laws of the old Scottish Parliament, and the main thesis of the study is the evolutionary nature of the provisions constituting the Court of Sessions which, on the one hand, were a continuation of the King’s previous jurisdictional powers and, on the other hand, were part of a wider trend towards separation of central courts from the royal councils in European monarchies.
Keywords: Sąd Sesji; prawo szkockie; postępowanie cywilne; jurysdykcje mieszane